THEORETICAL STUDY OF SOLVENT EFFECTS AND NMR SHIELDING TENSORS OF DLPC - M. Monajjemi; S. Afsharnezhad; M.R. Jaafari; S. Mirdamadi; H. Monajemi; S. Mollaamin (Universitas Gadjah Mada, 2008)
The effect of the polarity of the environment on the conformation zwitterionic membrane dilauroyl phosphatidylcholine (DLPC) has been investigated with calculation at the Hatree-Fock level using the 6-31G* basis set with Onsager continuum solvation model. The ‘Gauge Including Atomic Orbital' (GIAO) approach is used to investigate Ab initio GIAO calculations of NMR chemical shielding tensors carried out within SCF-Hartree-Fock approximation are described. In order to compare the calculated chemical shifts with experimental ones, it is important to use consistent nuclear shielding for NMR reference compounds like TMS. Conformation of DLPC was evaluated with four different solvents with different dielectric constant (Water (ε = 78.39), Dimethyl Sulfoxide (ε = 46.7), Acetone (ε = 20.7) and Heptane (ε = 1.92). In concern with conformational energy, Water could be the most suitable solvent for DLPC. Moreover, as the polarity of the medium increase, the conformational stability of this molecule increases faster than that of DLPC in the gas phase. Consequently, the relative energy of DLPC also depends on the polarity of the environment. This subject was considered as well as the most variable in some dihedral angles degree and NMR isotropic shift were in the less dielectric constant (ε = 1.92). It could be in polar medium DLPC conformer becomes additionally stabilized by intermolecular ionic and hydrogen bond interactions with polar neighboring molecules. On the basis of this work it can be concluded that the effect of the polarity of the environment clearly are influenced on the isotropic values by geometry variation due to intermolecular motion in molecule.